2013
DOI: 10.1137/110854394
|View full text |Cite
|
Sign up to set email alerts
|

First-Fit Coloring of Incomparability Graphs

Abstract: One of the simplest heuristics for obtaining a proper coloring of a graph is the first-fit algorithm. First-fit visits each vertex of the graph in the specified order and assigns to every point the least possible number. Let G be a class of incomparability graphs with bounded maximum clique size, closed under taking induced subgraphs. We prove that first-fit uses a bounded number of colors on the graphs in G iff there is an incomparability graph of clique size 2 not contained in G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This problem seems structurally similar to the problem of 3colouring a graph formed by a union of three incomparability graphs. However, existing results on incomparability graphs (see, e.g., Bosek, Krawczyk, and Matecki 2013) do not seem to be directly applicable to our problem.…”
Section: Voter Partitionmentioning
confidence: 85%
“…This problem seems structurally similar to the problem of 3colouring a graph formed by a union of three incomparability graphs. However, existing results on incomparability graphs (see, e.g., Bosek, Krawczyk, and Matecki 2013) do not seem to be directly applicable to our problem.…”
Section: Voter Partitionmentioning
confidence: 85%
“…A poset constructed during a regular game of width w is L 2w 2 −ladder-free, see Figure 19. As ladders are of width 2, we deduce that First-Fit uses bounded number of chains in a regular game of width w. However, bounding functions proposed in [6] are not polynomial. Therefore, it would be desirable to answer the following questions.…”
Section: Open Problemsmentioning
confidence: 93%
“…In [15] Kierstead showed a countable poset of width 2 on which First-Fit uses infinitely many chains. In [6] Bosek, Krawczyk and Matecki noted that this poset contains all finite posets of width 2. They also showed that for every finite poset Q of width 2 there exists a function f Q : N → N such that FirstFit uses at most f Q (w) chains on Q-free posets of width w (a poset P is Q-free if it does not contain an induced poset isomorphic to Q).…”
Section: Open Problemsmentioning
confidence: 99%
“…[2]). For every poset Q of width 2, there is a function f Q such that every poset P of width w that does not contain Q as an induced subposet satisfies Γ (P) f Q (w).…”
Section: Conjecturementioning
confidence: 99%